Iatrogenic displacement of mandibular third molar into the submandibular space. A case report and a suggested management procedure - M. Konate; K. Coulibaly; D. Sarfi; F. Slimani (Elsevier, 2023)
Background: Iatrogenic displacement of third molars in the mandibular floor is one of the rare complications of 3rd molar extractions. it is due to a variety of factors, most often anatomical or due to the operator. It's important to remain calm and opt for the best possible treatment when faced with such an accident. Case presentation: We report a case of iatrogenic 3rd molar displacement in the submandibular space managed by an extra-oral approach. Conclusion: Given the low incidence of iatrogenic tooth displacement in the mandibular region, there is no consensus on its management. We propose a decision tree for managing expulsed teeth in the submandibular region.